A Make-or-buy Decision Process for Outsourcing - Bajec, Patricija; Jakomin, Igor (Promet - Traffic&Transportation, 2012)
Should firms perform logistics services on their own or should they buy them from a logistics provider? Today’s global competition forces companies to re-evaluate their existing processes, technologies and services in order to focuse on strategic activities. Outsourcing is now increasingly used as a competitive weapon in today’s economy. External parties can often do job quicker, cheaper and better. This has resulted in an increasing awareness of the importance of the make-or-buy decision, the dilemma organisations face when deciding between keeping logistics services in house or purchasing them from an outside logistics provider. This article provides a make-or-buy decision process methodology that any manager can implement – whatever the size or industrial type of the organization. The make-or-buy methodology is one of the most critical strategic decisions within logistics outsourcing and should be taken in a structured and consistent manner. A practical guide to this decision is a step-by-step guide to addressing make-or-buy decision in a consistent and structured manner. The high-level steps are as follows: • evaluate whether outsourcing is right for your company; • determine exactly what functions to outsource and the performance expectations; • use a well-defined professional selection process to evaluate and select which provider(s) are right for the job. KEY WORDS: logistics, logistics outsourcing, make-or-buy decision, outsourcing methodology